L-Myc protein synthesis is initiated by internal ribosome entry - JOPLING, CATHERINE L. (Copyright 2004 by RNA Society, 2004)
An internal ribosome entry segment (IRES) has been identified in the 5′ untranslated region (5′ UTR) of two members of the myc family of proto-oncogenes, c-myc and N-myc. Hence, the synthesis of c-Myc and N-Myc polypeptides can involve the alternative mechanism of internal initiation. Here, we show that the 5′ UTR of L-myc, another myc family member, also contains an IRES. Previous studies have shown that the translation of mRNAs containing the c-myc and N-myc IRESs can involve both cap-dependent initiation and internal initiation. In contrast, the data presented here suggest that internal initiation can account for all of the translation initiation that occurs on an mRNA with the L-myc IRES in its 5′ UTR. Like many other cellular IRESs, the L-myc IRES appears to be modular in nature and the entire 5′ UTR is required for maximum IRES efficiency. The ribosome entry window within the L-myc IRES is located some distance upstream of the initiation codon, and thus, this IRES uses a “land and scan” mechanism to initiate translation. Finally, we have derived a secondary structural model for the IRES. The model confirms that the L-myc IRES is highly structured and predicts that a pseudoknot may form near the 5′ end of the mRNA.